PENINGKATAN PRODUKSI DAN PEMASARAN KELOMPOK USAHA JAJE ULI DAN BEGINA DI DESA PANJER DENPASAR - Luh Kadek Budi Martini; Mutria Farhaeni; Luh Komang Candra (Universitas Mataram, 2023)
Panjer village has 30 jaje offering business units (ceremonies). The objectives of the Beginner Community Empowerment activities are described as follows: (1) Availability of jaje uli & begine dryers as an effort to increase production; (2) Availability of slicing tools to increase jaje uli production; (3) Partners have knowledge and skills in product packaging; (4) Partners have knowledge and skills in product innovation; (5) Partners have knowledge and skills in using social media as promotional media. The methods used to increase production and marketing of the Jaje Uli and Begina businesses in Panjer Village are counseling, training and mentoring. Solutions to problems faced by partners are carried out through training and mentoring that uses science and technology according to the priorities and targets of Empowering Beginner Communities covering production and marketing aspects. During holidays, orders can reach 10,000 pieces in 2 days, due to limited production equipment, so only 5,000 can be fulfilled during the summer, but during the rainy season, they cannot fulfill them because there is no production. With a slicing machine, businesses produce 6 kg which takes 6-10 hours if they are not focused and with a slicing machine they can finish it in just 3 hours. 1kg produces 200pcs of jaje so 6kg will produce 1,200pcs. By carrying out technological innovations in production, product innovation and marketing content creation in order to be competitive, not only within the region but also outside the Panjer Village area.